Effects of cocoa pod husk (Theobroma cacao sp.) powder as an ingredient in bread roll. - Regulacion, Sheena Kate B. (2023.)
Bread is an essential part of Filipino tradition and lifestyle, regularly consumed by Filipinos. However, due to the price increase of essential commodities, such as flour and the shift in food trends, much research has been conducted to produce alternatives or substitutes to flour. This study used cocoa pod husk from Forastero and Trinitario cacao varieties in three bread roll formulations: A (10% cocoa pod husk powder, 90% bread flour), B (20% cocoa pod husk powder, 80% bread flour), and C (30% cocoa pod husk powder, 70% bread flour). The powder has desirable properties for reducing microbial growth and use in food formulation. A preference ranking test was conducted on three bread formulations. Physico-chemical and sensory properties of each bread formulation, including a control, were analyzed. Results showed increasing cocoa pod husk powder in the bread raised water activity and hardness, while decreasing height and weight, indicating its effective use in small amounts. The bread with the highest cocoa pod husk powder level had a darker appearance and moderate cocoa aroma compared to the control bread. Panelists preferred the bread with the lowest cocoa pod husk powder level, indicating its suitability for bread rolls at a 10% addition. Consumer acceptability tests found no significant differences in overall acceptance, taste, and texture between the control bread and the preferred formulation, indicating similar characteristics in these aspects. However, noticeable differences in color and odor were observed. Proximate composition analysis showed differences in moisture, ash, protein, and fiber content between the control and preferred formulation, but no significant differences in fat and carbohydrate content. Overall, cocoa pod husk powder has potential as a valuable ingredient in enhancing bread rolls, offering economic advantages over bread flour. The study demonstrates that the powder can improve sensory attributes and nutritional composition depending on the amount added.
Thesis (Undergraduate, Bachelor of Science in Food Technology) School of Technology, University of the Philippines Visayas, Miagao, Iloilo. 2023.
Keywords: Cocoa pod husk